Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The function given is

$f(x,y,z) = \displaystyle\frac{1}{(x+y+z+1)^2}$

$D = \{(x,y,z) \in \mathbb{R}^3 : x \geq 0, y \geq 0, z \geq 0, x+y+z \leq 1 \}$

It seems that the domain would be the under a plane that contains the points $(1,0,0)$, $(0,1,0)$, $(0,0,1)$; then if i consider the plane $XZ$ i have the set $D_{XZ}= \{(x,z) : z=1-x, 0 \leq x \leq 1 \}$ also $D_{XY}= \{(x,z) : y=1-x, 0 \leq x \leq 1\}$ and $D_{YZ}= \{(x,z) : z=1-y, 0 \leq y \leq 1\}$.

Then i could set $0\leq x\leq z-1$, $0\leq y\leq z-1$ and $0\leq z\leq 1$, and the integral would be given by:

$$\begin{align*} \displaystyle\int\displaystyle\int\displaystyle\int_D f(x,y,z)\,dx\,dy\,dz &= \displaystyle\int\displaystyle\int\displaystyle\int_D \displaystyle\frac{1}{(x+y+z+1)^2}\,dx\,dy\,dz \\&= \displaystyle\int_0^1\displaystyle\int_0^{1-z}\displaystyle\int_0^{1-z} \displaystyle\frac{1}{(x+y+z+1)^2}\,dx\,dy\,dz \\ &= -\displaystyle\int_0^1\displaystyle\int_0^{1-z} \bigg(\displaystyle\frac{1}{(1-z)+y+z+1)}- \displaystyle\frac{1}{(0)+y+z+1)}\bigg)\,dy\,dz \\ &= -\displaystyle\int_0^1\displaystyle\int_0^{1-z} \bigg(\displaystyle\frac{1}{y+2}- \displaystyle\frac{1}{y+z+1}\bigg)\,dy\,dz \\ &= -\displaystyle\int_0^1 (\log(y+2)-\log(y+z+1))|_{y=0}^{y=1-z}\,dz \\ &= -\displaystyle\int_0^1 \{[(\log(3-z)-\log(2)] - [\log(2)-\log(z+1)]\}\,dz \\ &= -\displaystyle\int_0^1 [(\log(3-z)+\log(z+1)-2\log(2)]\,dz \\ &= 2\log(2)+\{[(3-z)\log(3-z) \\ & \;\;\;- (3-z)]|_{z=0}^{z=1} - [(z+1)\log(z+1)-(z+1)]|_{z=0}^{z=1}\} \\ &= 2\log(2) - 3\log(3) +4 \end{align*} $$

Did i solved it correctly?

share|cite|improve this question
up vote 1 down vote accepted

I don't think so. I think the integral looks like

$$\int_0^1 dx \, \int_0^{1-x} dy \, \int_0^{1-x-y} dz \frac{1}{(1+x+y+z)^2}$$

which is equal to

$$-\int_0^1 dx \, \int_0^{1-x} dy \, \left [\frac{1}{2} - \frac{1}{1+x+y} \right ]$$

which is equal to

$$-\int_0^1 dx \, \left [\frac12 (1-x) - \log{2} + \log{(1+x)} \right ] $$

which in turn is equal to

$$-\frac14 + \log{2} - \left [ (1+x) \log{(1+x)} - (1+x)\right]_0^1 = \frac{3}{4}-\log{2}$$

This result was verified in Mathematica.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.